THU0685 THE IMPACT OF ACHIEVEMENT OF RESPONSE AT ONE YEAR AFTER STARTING THERAPY ON THE LONG-TERM OUTCOME OF LUPUS NEPHRITIS. (June 2019) - Saccon, Francesca; Gatto, Mariele; Frontini, Giulia; Messa, Piergiorgio; Tamborini, Francesco; Pieruzzi, Federico; Radice, Francesca; Quaglini, Silvana; Sinico, Renato Alberto; Vaglio, Augusto; Moroni, Gabriella; Doria, Andrea
Abstract : Background: A variable percentage of lupus nephritis (LN) patients (pts) achieve response after the start of induction therapy. The impact of response on long-term renal outcome of LN is still unclear. Objectives: To establish the response rate at one year after starting induction therapy and its impact on long-term development of chronic kidney disease (CKD) in LN. Methods: 381 biopsy proven LN pts (86% females, mean age 31.3±12.1years), (18 pts:class II; 88 pts:class III; 199 pts:class IV; 76 pts:class V ISN/RPS) with estimated glomerular filtration rate (eGFR) 89.8±40.4 and proteinuria 4.3±3.9g/24h entered this study. As induction therapy, pts received methylprednisolone pulses (72%), oral prednisone (28%), cyclophosphamide (55%), mycophenolate mofetil (24%), azathioprine (5, 5%), other immunosuppressants (15.5%). During a follow-up of 13.5 years after LN diagnosis, 53 pts (13.9%) developed CKD and 22 (5.8%) died. Definitions: Complete response (CR) at one year: eGFR>60ml/min and proteinuria< 0.5/die, partial response (PR): eGFR>60ml/min, 50% reduction of proteinuria to sub-nephrotic range, no response (NoR): all the other cases. Survival curves were drawn using the Kaplan-Meier estimate and compared using the log-rank test. Cox regression model was used to test variables at univariate and at multivariate analysis. Results: One year after the start of therapy, 220 pts (58%) achieved CR, 100 pts (26%) PR and 61 pts NoR. CKD developed in 11 out of 220 CR pts (5%), 18 out of 100 PR pts and 24 out of 61 NoR (39%). CKD free survival at 5, 10, 15 and 20 years were 99.5%, 96.5% 95.2% and 92.5 in CR pts, 99%, 90%, 87, 6% and 83% in PR pts, and 81%, 65%, 54% and 44% in NoR pts (p<0.0001). In detail: CR vs RP p=0.067, RP vs NoR p<0.0001, and CR vs NoR p<0.0001. We have searched for the predictors of NoR among the clinical/therapeutic characteristics at diagnosis of LN. At univariate analysis, chronicity index at renal biopsy (p=0.0001), serum creatinine (p=0.001), eGFR (p=0.036), presentation with nephritic syndrome or rapid progressive renal failure (p=0.02), serum albumin (p=0.02) and arterial hypertension (p=0.001), were the predictors of NoR at one year. At multivariate analysis chronicity index (p=0.013) and arterial hypertension (p=0.017) were the independent predictors. Conclusion: The achievement of CR or PR at one year is associated with preservation of renal function in the long-term. For this reason, any effort should be made to achieve response. Patients with impaired renal function, with high chronicity index at renal biopsy and arterial hypertension should be more tightly monitored as they have the highest risk of NoR. Disclosure of Interests:  :   None declared